The Art of Artificial Evolution - Romero, Juan (Springer, 2017)
While improvements in computer performance are dramatically changing the computer-generated art industry, scientists in natural computing have teamed up with artists to examine how bioinspired systems can influence art, technology and even aesthetic appreciation. This comprehensive book gives an up-to-date survey of the relevant bioinspired computing research fields – such as evolutionary computation, artificial life, swarm intelligence and ant colony algorithms – and examines applications in art, music and design. The editors and contributors are researchers and artists with deep experience of the related science, tools and applications, and the book includes overviews of historical developments and future perspectives. The book will be of interest to computer scientists and artists engaged with natural computing techniques applied to art, music and design. The book is supported with a dedicated website.